An antiempirical strategy: sacrificing aromatic moieties in the polymer precursor for improving the properties of the derived N-doped porous carbons - Qi, Shi-Chao; Xue, Ding-Ming; Yu, Guo-Xing; Zhu, Rong-Rong; Liu, Xiao-Qin; Sun, Lin-Bing (Green chemical engineering, 2020)
With the carbonization at an elevated temperature, high aromaticity of a precursor for porous carbons was traditionally thought to be crucial for the resultant perfect textural properties and ideal application performances of the porous carbons. Thus, many efforts have been done to search or to artificially prepare the polymer precursors with higher aromaticity to generate more satisfying porous carbons. However, an antiempirical case was found in this study. The copolymerization between 1,3,5-tris(chloromethyl)-2,4,6-trimethylbenzene (TCM) and cyclohexane-1,4-diamine was successfully implemented to get a polymer code-named NUT-40, in which half of the ring structures are nonaromatic, while N-doped porous carbons (NDPCs) with better textural properties (e.g., SBET = 1363 m2 g−1 for NDPC-600) and competitive CO2 capture abilities (e.g., CO2 capacity = 4.3 mmol g−1 at 25 °C and 1 bar for NDPC-600) were generated from the NUT-40, compared with the NDPC counterparts derived from the NUT-4 in a previous study (e.g., SBET = 958 m2 g−1 and CO2 capacity = 3.8 mmol g−1 at 25 °C and 1 bar for NDPC-600), in which TCM and ursol were employed as the monomers instead, and thus the ring structures in the NUT-4 was fully aromatic. With first-principle and molecular dynamics simulations, it was demonstrated that the embryo pore structure in the NUT-40 molecule can be more easily maintained during the carbonization than that of the NUT-4, which finally improves the surface area and porosity of the NUT-40 generated NDPCs. [Display omitted] •A polymer precursor containing large number of aliphatic rings is fabricated.•Aliphatic rings of the polymer precursor improve the derived NDPCs.•First-principle and MD simulations reveal the underlying mechanisms.•The derived NDPCs perform on selective carbon capture very well.